CLINICAL MANIFESTATIONS OF TRAUMATIC INTRACRANIAL HEMATOMAS WITH DIFFERENT OUTCOMES - G. V. Anisimov; Y. I. Kravtsov (Klinicist, 2014)
Aim – clarification of the clinical progression nature of traumatic intracranial hematoma.Materials and methods. A comparative evaluation of neurological status, vegetative tone, level of stress (SL), and consciousness in 42 menwith different outcomes on neuroreanimation stage.Results. It is shown that in the group of survivors by raise of the level of consciousness focal neurological symptoms come to the fore, revealed on the 10th day in 78.4 % of patients. In the case of lethal outcome to 7–9th day from decompensation and reduce consciousness to atonic stem symptoms prevailed coma at almost all patients. SL and Kerdo index proved to be reliable outcome indicators of acute period of severe traumatic brain injury (TBI). Thus, the preservation of SL and sympathic to the maximum levels for > 5 days served as a poor prognostic sign.Conclusion. In addition to the assessment of consciousness and neurological status in the most acute period of TBI a comprehensive study of laboratory indicators of stress reactions should be included in the diagnostic algorithm which will allow to determine compensatory mechanisms status, to predict their changes and the deterioration of the patient.